Finding the Best Technique to Transfer from Geosynchronous Transfer Orbit (GTO) to Lunar Orbit - ALnidawi, Marwah Issa Abood; Saleh, Abdul-Rahman H. (Iraqi Journal of Science, 2025)
To assess various methods for relocating a fictional satellite from a geosynchronous transfer orbit (GTO) to a lunar orbit, this research project was conducted. The primary objective of the study was to determine the most time and cost-effective technique, while also considering the influence of perturbations and other possible variables on orbital mechanics analysis. Three different approaches were examined, involving the transfer of the satellite in one, two, or three separate rounds. The development of algorithms for this investigation relied on MATLAB orbital mechanics software, and careful consideration was given to factors such as delta-v, mission duration, spacecraft mass, and potential perturbations throughout the course of the transfer. For each mission’s requirements, the study discovered that every technique had its own set of benefits and drawbacks. The least time-consuming and the easiest way was the first technique, despite using up the largest amount of propellant. The second technique might find a middle ground between propellant usage and mission time. Even though it took longer, the third technique consumed less propellant than the first two techniques. The fourth technique proved advantageous in terms of propellant usage and mission time. Factors such as atmospheric drag, perturbations from other celestial bodies, and solar radiation pressure can affect the spacecraft’s trajectory and require additional analysis to ensure the success of the mission. The study also emphasized the impact of these perturbations on the spacecraft’s path, potentially necessitating course corrections and increasing propellant usage. The most pronounced effects on the orbital elements were discovered to stem from the Earth’s oblateness, primarily impacting perigee and apogee. Providing insights into various mission requirements and perturbations, this study revealed the most efficient technique for transferring a satellite from the geosynchronous transfer orbit (GTO) to the lunar orbit.